Handwerk im Wettbewerb Handwerksunternehmen im EU-Beihilfenrecht und im Recht der öffentlichen Unternehmen - Pöhlmann, Marius (Wirtschaft und Recht für Mittelstand und Handwerk, 2023)
The crafts sector is of great economic importance in Germany and is indispensable for mastering a multitude of current and future challenges. At the same time, it is subject to a legal regime that is unique in Europe. This article examines the impact of this unique legal regime in selected areas of public competition law, in particular state aid law and public enterprise law. It examines how the combination of typical regulatory and trade law with competition law shaped by European Union law affects the competitive position of craft enterprises. Legal policy proposals will also be developed and measured against the higher law.